2012
DOI: 10.1186/1746-6148-8-128
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive phosphorylation of the mTORC2/Akt/4E-BP1 pathway in newly derived canine hemangiosarcoma cell lines

Abstract: BackgroundCanine hemangiosarcoma (HSA) is a malignant tumor with poor long-term prognosis due to development of metastasis despite aggressive treatment. The phosphatidyl-inositol-3 kinase/Akt/mammalian target of rapamycin (PI3K/Akt/mTOR) pathway is involved in its endothelial pathologies; however, it remains unknown how this pathway plays a role in canine HSA. Here, we characterized new canine HSA cell lines derived from nude mice-xenografted canine HSAs and investigated the deregulation of the signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 48 publications
(93 reference statements)
2
63
0
Order By: Relevance
“…p-S6 is expressed in cases with PIK3CA or PTEN mutations (Fig 6B), indicating activation of the PI3K/AKT/mTOR cascade. Our findings agree with previous studies which showed that the PI3K and MAPK pathway were frequently activated in canine HSA [20,22], and our mutational data provide molecular mechanisms for these phenotypes. IHC analysis of p-ERK, p-AKT and p-S6 in HSA cases is summarized in S3 Table.…”
Section: Plos Onesupporting
confidence: 93%
“…p-S6 is expressed in cases with PIK3CA or PTEN mutations (Fig 6B), indicating activation of the PI3K/AKT/mTOR cascade. Our findings agree with previous studies which showed that the PI3K and MAPK pathway were frequently activated in canine HSA [20,22], and our mutational data provide molecular mechanisms for these phenotypes. IHC analysis of p-ERK, p-AKT and p-S6 in HSA cases is summarized in S3 Table.…”
Section: Plos Onesupporting
confidence: 93%
“…The mTOR pathway is present and active in various immortalized canine cell lines such as osteosarcoma, 9 hemangiosarcoma, 10,11 and malignant melanoma. 12 Exposure of those cell lines to rapamycin results in a significant, dose-dependent decrease in viable tumor cells.…”
mentioning
confidence: 99%
“…29 Furthermore, a total of seven canine AS cell lines were established from three different xenograft canine tumors. 30 Although there are a number of AS cell lines derived from cutaneous tumors, so far only one cell line has been generated from hepatic AS. 31 This cell line named HAEND was established from a post-mortem liver biopsy of a patient diagnosed with hepatic AS induced by vinyl chloride, a well-known causal agent.…”
Section: Discussionmentioning
confidence: 99%